College students and financial distress: exploring debt, financial satisfaction, and financial anxiety - Archuleta, Kristy L.; Dale, Anita; Spann, Scott M. (My University, 2014)
The impact of financial concerns on overall mental health has become a popular topic among researchers and practitioners. In this exploratory study, possible associations of financial anxiety were explored using a sample of 180 college students who sought services at a university peer financial counseling center in a Midwestern state. Of particular interest was the influence of debt on student financial anxiety. To measure financial anxiety, a new scale was developed, the Financial Anxiety Scale (FAS), that can be used as a tool for financial planners, counselors, and educators to identify individuals who are experiencing increased levels of financial distress that may call for a referral to an appropriate professional. Results from two hierarchical regressions indicated that financial satisfaction, student loans, and gender are associated with financial anxiety.
Keywords: Financial anxiety; Financial counseling; Financial satisfaction; Financial scale; Student debt